POTRET PROSES KEWIRAUSAHAAN DARI PERINTISAN SAMPAI PENGEMBANGAN USAHA SEBUAH UKM DALAM MENUJU PASAR INTERNASIONAL - Suharti, Lieli; Untoro, Hendy (Proceeding SENDI_U, 2016)
Not many SMEs in Indonesia are able to enter the international market. Even if there is, still in limited quantities.This study was conducted to determine how the strategy of an SME whom able to penetrate the international marketin a relatively short time. This research is a case study using a qualitative approach. Object of this study is an SMEin Semarang district, Central Java which is engaged in the business that produces charcoal briquettes made fromcoconut shell. The products has been exported to various countries in Europe and America. Based on the resultsobtained through in-depth interview from number of key informans, shows that the success of SMEs for enteringinternational markets is highly dependent on the entrepreneurial process in the pioneering and development stagesof the business. A number of internal factors of the business owners as well as external factors such as marketopportunities, networking, and government support was found as driving factors behind the success of an SME toenter international markets.Keywords: Entrepreneurial Process, Internal Driving forces, External Driving forces, SME, International market